Implementation of the 5s program in a civil construction material warehouse - Carmo Neto, Messias Camilo do; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2024)
The 5S program is a tool aimed at rationalizing resources and reorganizing the work environment, leading to improvements and ensuring the practice of quality management. This work is the result of a study developed in the sales and production of a civil construction materials depot, and its objectives are summarized in its implementation. Surveys and structured interviews were applied to identify the main failures causing poor organization in the work environment, and subsequently, an action plan was carried out using the PDCA methodology for the implementation of 5S in the store’s departments, stock, and manufacturing in the sawmill sector. The results obtained after application were quite significant, showing that organization in the work environment improved significantly, bringing greater participation, discipline, and commitment of the employees to the company. Thus, the importance of applying quality tools aimed at continuous improvement as a growth strategy was proven.